2021
DOI: 10.1055/s-0041-1729562
|View full text |Cite
|
Sign up to set email alerts
|

Bioresilience to Mercury Chloride of the Brine Shrimp Artemia Salina after Treatment with Homeopathic Mercurius Corrosivus

Abstract: Introduction Finding solutions to mitigate the impact of pollution on living systems is a matter of great interest. Homeopathic preparations of toxic substances have been described in the literature as attenuation factors for intoxication. Herein, an experimental study using Artemia salina and mercury chloride was developed as a model to identify aspects related to bioresilience. Aims The aim of the study was to describe the effects of homeopathic Mercurius corrosivus (MC) on Artemia salina cysts hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 79 publications
(130 reference statements)
2
30
0
Order By: Relevance
“…25 In Pinto et al, 2021, treating 20,000 cysts exposed to mercury chloride at 10% lethal concentration with the respective isotherapic prolonged the diapause period, protecting the embryos from direct contact with the toxic substance up to its evaporation. 22 Similar studies using high potencies of homeopathic arsenic performed in plants and microorganisms have shown similar effects. [26][27][28] Given that such homeopathic dilutions often exceed the limit of Avogadro's number, it is necessary to consider the possible existence of mechanisms other than purely biochemical ones to explain the observed protective effects described above.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…25 In Pinto et al, 2021, treating 20,000 cysts exposed to mercury chloride at 10% lethal concentration with the respective isotherapic prolonged the diapause period, protecting the embryos from direct contact with the toxic substance up to its evaporation. 22 Similar studies using high potencies of homeopathic arsenic performed in plants and microorganisms have shown similar effects. [26][27][28] Given that such homeopathic dilutions often exceed the limit of Avogadro's number, it is necessary to consider the possible existence of mechanisms other than purely biochemical ones to explain the observed protective effects described above.…”
Section: Introductionmentioning
confidence: 67%
“…are deemed to be nonsentient organisms, which significantly facilitates the ethical aspects involving their use in research. 10,21 Recently, we have observed bioresilience processes in a model of Artemia salina cyst hatching by inserting isotherapic potencies of toxic agents into the culture water, [22][23][24] being prepared according to the official homeopathic pharmacopeia. 25 In Pinto et al, 2021, treating 20,000 cysts exposed to mercury chloride at 10% lethal concentration with the respective isotherapic prolonged the diapause period, protecting the embryos from direct contact with the toxic substance up to its evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Sunlight may play a part in potency degradation in the natural world, but the sustained action of Phosphorus 30 in a large lake system 8 subject to sunlight over several days suggests it cannot be the sole agent responsible for potency decay. Indeed, results with a large number of solvatochromic dyes under conditions where light is largely excluded 1 2 3 4 5 6 7 8 9 provide ample evidence that potency action slowly decays in the presence of dye, irrespective of the absence of light, indicating that the potency–solvatochromic dye interaction itself eventually causes potency decay.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown solvatochromic dyes to be consistently useful in investigating the physico-chemical nature of homeopathic potencies. [1][2][3][4][5][6][7][8][9] So far, investigations have focused on using free dyes in solution and how the spectra of those dyes change on interacting with a range of remedies of differing potency levels. Whilst a great deal of information has so far been gained using this approach, most solvatochromic dyes in aqueous solution are subject to varying degrees of aggregation, dependent upon dye structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some homeopathic preparations have been identified as remedial action on toxicity models in Artemia salina. This study aimed to observe whether homeopathic products influence the toxicity of R. raciborskii extract on A. salina by inducing cyst hatching arrest, an embryo bioresilience model previously developed in our laboratory (Pinto et al, 2021; Mohammad et al, 2022). Thus, previous toxicity tests were carried out on cysts in 96-well plates, using different concentrations of the extract obtained from regular cultivation of R. raciborskii in HCl 0.05M, whose strain, named T3, is kept in the laboratory of Cyanobacteria at FURGS, Brazil.…”
mentioning
confidence: 99%